The diversity of cellular systems involved in carbonate precipitation by Escherichia coli - Matthew E. Jennings; George J. Breley; Reilly S. Blackwell; Anna Drabik; Kathleen R. Gisser; Joe Kainrad; Victoria Ligman; Jaycie Proctor; Rose Deshler; Brian A. O’Hart; Arlyn Rivera; Lorelei Centrella; et al. (PLoS ONE, 2025)
Climate change is increasing the need to limit levels of anthropogenic CO 2 released into the atmosphere. One approach being investigated is to generate products based on microbially induced carbonate precipitation (MICP), which can trap CO 2 as CaCO 3 . We recently identified a novel MICP pathway in bacteria that is initiated by Ca 2+ toxicity in cells, causing extracellular CO 2 to be trapped as CO 3 2- by Escherichia coli, although the yield of precipitated CaCO 3 remained low (in the milligram range). In this work, we used the E. coli Keio gene knock-out library to identify 54 genes involved in MICP in E. coli, which could be broadly characterized into four groups: central metabolism, iron metabolism, cell architecture, and transport. The role of central metabolism appears to be crucial in maintaining alkaline conditions surrounding the cell that promote CaCO 3 precipitation. The role of iron metabolism was less clear, although the results suggest that growth rate influences the initiation of MICP. While the impact of repeating polymeric structures on cell surfaces promoting MICP is well established, our results suggest that other structural features may play a role, including fimbriae and flagella. Finally, the results confirmed that Ca 2+ transport is central to MICP under calcium stress. The results further suggest that the ZntB efflux pump may play a previously unidentified role in Ca 2+ transport in E. coli. By overexpressing some of these genes, our work suggests that there are several previously unidentified cellular mechanisms that could serve as a target for enhanced MICP in E. coli. By incorporating these processes into MICP pathways in E. coli, it may be possible to increase the volume of CO 2 fixed using this pathway and yield potentially new products that can replace CO 2 intensive products, such as precipitated calcium carbonates (PCCs) for industry.